Electoral malpractice - Birch, Sarah, 1963-; European Consortium for Political Research (Oxford : Oxford University Press, 2011)
'Electoral Malpractice' shows how this phenomenon might be reduced by means of a variety of strategies designed to raise the cost of electoral manipulation by increasing the ability of civil society and international actors to monitor and denounce it.
At foot of title: ECPR.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Elections -- Corrupt practices